The Analysis of Family Planning Participation at The Initial Period Of Covid-19 Pandemic - Indrayani, Triana; Niklah, Niklah; Lail, Nurul Husnul (STRADA : Jurnal Ilmiah Kesehatan, 2021)
As many as 100 respondents were involved in the current study and chosen through proportional stratified random sampling technique at Bakti Jaya Public Health Center from January to November 2020. The research instrument used a questionnaire obtaining primary data which were analyzed using Chi Square statistical test. The univariate analysis conducted showed that among 100 mothers, 64% had low education level, 71.0% had poor knowledge, 68% had negative attitudes, 62% suffered from anxiety disorder, 75.0% were going through PSBB, 62.0% were not supported by their husband, and 75% were supported by health workers. Furthermore, the bivariate analysis presented that there was a relationship between education (p = 0.000), knowledge (p = 0.000), attitudes (p = 0.000), anxiety (p = 0.000), large-scale social restrictions (PSBB) (p = 0.000), 0.000 husbands' support, and health workers' support (p = 0.004) with the family planning participation in the initial period of COVID-19 pandemic